Cystic fibrosis: Correction of a fatal disease - Jeffrey M. Friedman (Proceedings of the National Academy of Sciences, 2025)
The 2025 Lasker~DeBakey Clinical Medical Research Award has been given to Michael Welsh, Jesús (Tito) González, and Paul Negulescu for their key roles in developing a novel treatment for cystic fibrosis (CF)—a three-drug combination that saves the lives of people with this lethal genetic disease [D. Keating et al. , N. Engl. J. Med. 379, 1612–1620 (2018)]. The disease is caused by mutations that disrupt the function of a gene known as CF Transmembrane Conductance Regulator which encodes a chloride channel expressed in epithelial cells including the lung. Collectively the three recipients were responsible for the development of novel high-throughput drug screens that led to the development of the new drugs. Welsh is a pulmonologist who played a key role in understanding the physiology and pathophysiology of the disease. González is a physical organic chemist who developed a novel technology that enabled robust high-throughput screens for drugs that correct the channel defects. Negulescu led a group of extremely talented biologists, chemists, and physicians who built on these advances to develop novel three-drug combinations that have miraculous benefits for the majority of afflicted patients. This advance represents a true milestone in medicine and fulfills a dream of research scientists and families—the conversion of a fatal disease into a fully treatable one. It is also a stunning example of the power of medical research to save people’s lives.